Strengthening the Role of Human Resources in Sharia Financial Institutions in Indonesia - Muhammad Agung Miftah Syamsul; Muhammad Adnan Fajrin; Rika Dwi Ayu Parmitasari; Alim Syariat (GoodWill, 2024)
The success of Islamic financial institutions is highly dependent on the active contribution of industry players in improving service quality and customer satisfaction. However, the reality shows that these institutions are not yet supported by human resources who have adequate competence and professionalism in the field of sharia. This study aims to evaluate the current condition of human resources in Indonesian Islamic financial institutions, as well as to formulate strategic steps to strengthen their role. The findings of this study indicate the need for restructuring and improving employee competence in order to compete in the financial industry. To strengthen the role of these human resources, improvement efforts can be made through two approaches, namely managerial and legal. From a managerial perspective, Islamic financial institutions must have a structured system in employee planning, recruitment, and development that is in line with Islamic principles. Meanwhile, from a legal perspective, regulations are needed that regulate human resource management by considering religious character and compliance, and include terms, conditions, and supervision that are in accordance with the profile of Islamic institutions.